The pastoral office of priests and its relationship to the canonical institute of incardination - Keeler, Roger H (University of Ottawa (Canada), 2008)
The church's law dealing with incardination is a venerable ancient guarantor of its highest values with regard to community, holy orders, ministry, and the content of faith. By establishing a juridic protection for a permanent relational bond, incardination provides the context within which these are enabled to be vivid, dynamic, and reciprocally life/Life giving. Explored in light of the Legislator's intent as that was given shape and substance in the Post-synodal Apostolic Exhortation Pastores dabo vobis, incardination is lifted up from a flat uni-dimensional and somewhat narrow juridic plane, to become something rich and multi-dimensional. When this is combined with the work of Oblate theologian David N. Power, it is learned that incardination involves a series of attitudes that invite a range of spiritual and pastoral decisions that make koinonia (fellowship or collaboration; Christ's ministry of love), diakonia (service; Christ's ministry of service), martyrion (witness; Christ's proclamation of the word), and leitourgia (worship; the origin and ultimate end of Christ's entire ministry)---the God-life---possible. This leads to the formulation of a new definition for incardination that pushes doors ajar inviting new exploration. The Pastoral Office of Priests and its Relationship to the Canonical Institute of Incardination is a historical exploration into one of the church's oldest canonical institutes. By returning to the most fundamental of sources, the New Testament, it seeks to discover the root of a spiritual bond that identifies those in the ministerial priesthood. The Fathers of the Church are consulted, together with early conciliar decrees, and ordination rites extant in ancient times, in order to understand the pastoral bond that unites priests and their bishops. The Council of Trent and legislation found in the 1917 Codex Iuris Canonici are explored in order to learn the specific nature of the juridic bond formally called incardination. Pope John XXIII initiated a new fuller understanding of the theology of ordained ministry that was eventually reflected by the Conciliar Fathers in Presbyterorum ordinis, and enveloped in the 1983 Code of Canon Law. This is identified as a movement toward a unified understanding of incardination with implications for the church today.
Keywords: Religion, Clergy.; Canon Law.